Chicken soup for the soul : teens talk about growing up - Canfield, Jack (Cos Cob CT: Chicken Soup for the Soul, 2008)
stories about growing up, meeting challenges, and learning from life.
Keywords: Teenagers -- conduct of life -- anecdotes; Teenagers writings